Integrasi Ekspor Kopra Makassar di Antara Kontinuitas dan Diskontinuitas - Asba, A. Rasyid (UI Scholars Hub, 2006)
The study on Macassar Copra to date has not got much concern from Indonesian Historians, though it is realized that the commodity was the urgent in the world trading. This study constitutes a contribution to complement the shortcoming in this field, that is, in special manner, by spotlighting the integration of the islands in the eastern part of Indonesia, their relation with both Macassar and the world market. The focus of this study was the export of Macassar copra while its period limit was within 1883-1958. In this study, Macassar copra export was divided into two development stages. First, the expansion period and the second was contraction period. During the expansion period, the export of Macassar copra indicated a bright and amazing progress, while the contraction period showed the decline, vague and hopeless.